Evaluation of the image quality in computed tomography: different phantoms - Silveira, Vinícius C.; Oliveira, Larissa C.; Delduck, Rômulo S.; Kodlulovich, Simone; Mecca, Fernando A.; Silva, Humberto O. (Revista Brasileira de Física Médica, 2015)
The aim of this paper was to compare the simulators provided by the CT manufactures and Catphan’s Phantom with the American College of Radiology (ACR) computed tomography phantom. The image evaluation followed the protocols established by the manufactures of the phantoms. For slice thickness evaluation, the maximum percentage difference was 9% between the phantoms ACR and Siemens. In CT number accuracy test, the measurements of CT number of water showed a difference of 10 HU between the CT simulators. Comparing the uniformity results, the discrepancy was 11% and 55% for Siemens and Philips respectively in relation to the result obtained with the ACR phantom. The result of low contrast was the same for all phantoms. The MTF50 and MTF10 obtained with Siemens phantom was 4 and 8 pl/mm. For Catphan, 6 and 7 pl/mm. Results demonstrate that the ACR simulator was the most comprehensive and flexible to be used in several scanner models. Some simulators did not present all image quality indicators to perform a complete test.